Política educacional em retalhos A CAPES e a formação de professores da educação básica no Brasil - Neto, Nathanael da Cruz e Silva (Editora Oficina Universitária, 2021)
This book is the result of an important study carried out by Nathanael da Cruz e Silva Neto on the role of CAPES in contemporary policies for training Basic Education teachers. Through historical analysis, with the contribution of extensive bibliographical and documental research, the author focuses on the policies carried out by this important public institution, created in 1951, and linked to the Ministry of Education. Traditionally focused on postgraduate development, regulation and evaluation issues, the text situates and contextualizes, for the reader, the exact moment when CAPES is also shifted to the epicenter of the national teacher training policy, occupying a outstanding role in the field of formulation and execution of public policies for teacher training. Thus, in the context of the Brazilian federative arrangement and the collaboration regime, instituted by the Federal Constitution of 1988 and by LDBEN/1996, the "New CAPES" is elevated to the condition of an important agent in the coordination of national policies for initial and continued training of our teachers. The weaknesses and focus of policies, points out the study, are still the great challenge for the advancement of programs and teacher training goals. Finally, this book is an irresistible invitation for those who wish to know, in great detail, important milestones in the history of education and Brazilian educational policy.